Generation and optimization of the self‐administered bleeding assessment tool and its validation as a screening test for von Willebrand disease. (14th July 2015) - Deforest, M.; Grabell, J.; Albert, S.; Young, J.; Tuttle, A.; Hopman, W. M.; James, P. D.
<x xml:space="preserve">Abstract</x> Introduction/Aim Our aim was to generate, optimize and validate a self‐administered bleeding assessment tool (self‐BAT) for von Willebrand disease (VWD). Methods In Phase 1, medical terminology in the expert‐administered International Society on Thrombosis and Haemostasis (ISTH)‐BAT was converted into a Grade 4 reading level to produce the first version of the Self‐BAT which was then optimized to ensure agreement with the ISTH‐BAT. In Phase 2, the normal range of bleeding scores (BSs) was determined and test–retest reliability analysed. In Phase 3, the optimized Self‐BAT was tested as a screening tool for first time referrals to the Haematology clinic. Results Bleeding score from the final optimized version of the Self‐BAT showed an excellent intra‐class correlation coefficient (ICC) of 0.87 with ISTH‐BAT BS in Phase 1. In Phase 2, the normal range of BSs for the optimized Self‐BAT was determined to be 0 to +5 for females and 0 to +3 for males and excellent test–retest reliability was shown (ICC = 0.95). In Phase 3, we showed that a positive Self‐BAT BS (≥6 for females, ≥4 for males) has a sensitivity of 78%, specificity of 23%, positive predictive value (PPV) of 0.15 and negative predictive value (NPV) of 0.86 for VWD; these figures improved when just the females were analysed; sensitivity of 100%, specificity of 21%, PPV = 0.17 and NPV = 1.0. Conclusion We show an optimized Self‐BAT can generate comparable BS to the expert‐administered ISTH‐BAT and is a reliable, effective screening tool to incorporate into the assessment of individuals, particularly women, referred for a possible bleeding disorder.